2009
DOI: 10.1088/0022-3727/42/4/045106
|View full text |Cite
|
Sign up to set email alerts
|

About red afterglow in Pr3+doped titanate perovskites

Abstract: The red phosphor CaTiO3 : Pr3+ is known to show a persistent luminescence in the red spectral region upon irradiation in the UV. Although a number of studies have been dedicated to the enhancement of the afterglow efficiency in this perovskite by varying the preparation method, the chemical composition or the particle size, no clear explanation of the mechanisms involved in the afterglow process has been given yet. The purpose of this paper is to start investigating this aspect on the basis of a recently devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 25 publications
(47 reference statements)
7
71
0
Order By: Relevance
“…4 to elucidate the effect of Zr 4+ substitution on the afterglow. The profile and the location of the peak in the TL curve of CaTiO 3 :Pr 3+ are consistent with previous reports [25,26]. With the increase of the Zr concentration, the profile of the curve and the location of the peak have not changed distinctly in comparison with those of CaTiO 3 :Pr 3+ , indicating that the type of traps responsible for TL has not changed.…”
Section: Thermoluminescence and Possible Afterglow Mechanismsupporting
confidence: 90%
“…4 to elucidate the effect of Zr 4+ substitution on the afterglow. The profile and the location of the peak in the TL curve of CaTiO 3 :Pr 3+ are consistent with previous reports [25,26]. With the increase of the Zr concentration, the profile of the curve and the location of the peak have not changed distinctly in comparison with those of CaTiO 3 :Pr 3+ , indicating that the type of traps responsible for TL has not changed.…”
Section: Thermoluminescence and Possible Afterglow Mechanismsupporting
confidence: 90%
“…They suggested that the positive charged [Pr Ca ] o defect plays a capital role in the afterglow process of CPTO. The [Pr Ca ] o defects act as the trapping centers that can accept photoelectrons from the UV-excited states, resulting in the B excitation band and the afterglow [29]. The lower afterglow of films is due to a smaller number of absorbing and emitting Pr 3+ centers per illuminated surface unit.…”
Section: Resultsmentioning
confidence: 99%
“…irrespective whether excitation is in the host (320 nm), the IVCT band (370 nm), or the 4f level at 445 nm. Even down to 77K emission from the 3 P 0 is not observed 20 which means that T 0.5 must be near 0 K.…”
Section: The Titanatesmentioning
confidence: 94%